APPLICATION OF THE PROMETHEE II METHOD ON LECTURER RECIPIENTS OF UPI YPTK PADANG GRANTS - Mahessya, Raja Ayu Mahessya; Trisna, Novi (Jurnal Ipteks Terapan, 2023)
This research aims to apply the PROMETHEE II method in evaluating grant recipient lecturers at UPI YPTK Padang with the aim of providing final grade recommendations according to the passing grade. The PROMETHEE II method is used to overcome the complexity of decision making which involves many criteria, so that it can provide a more objective and accurate evaluation of the performance of grant recipient lecturers. Lecturer performance data consisting of templates, proposal content, output or publications, benefits of research grants, is collected for analysis using the PROMETHEE II method. Assessments based on each criterion are integrated and analyzed to produce a final score for each grant recipient lecturer. The research results show that the PROMETHEE II method provides final grade recommendations in accordance with the passing grade for each grant recipient lecturer. This assessment is based on the performance and contribution of each lecturer in various aspects of academic and research activities. The final grade recommendation can be used as a basis for making decisions regarding the graduation of grant recipient lecturers.